The Zionist ideas : visions for the Jewish homeland--then, now, tomorrow - Troy, Gil; Sharansky, Natan, 1948- (University of Nebraska Press, 2018)
"The most comprehensive Zionist collection ever published, The Zionist Ideas: Visions for the Jewish Homeland --Then, Now, Tomorrow builds on Arthur Hertzberg's classic The Zionist Idea, showcasing more than 170 visionaries and shedding light on the surprisingly diverse and shared visions for realizing Israel as a democratic Jewish state"-- Provided by publisher
"Published by the University of Nebraska Press as a Jewish Publication Society book."
Keywords: Zionism -- History -- Sources.; RELIGION -- Judaism -- History.; SOCIAL SCIENCE -- Jewish Studies.; HISTORY -- Middle East -- Israel.; POLITICAL SCIENCE -- Essays.; POLITICAL SCIENCE -- Government -- General.; POLITICAL SCIENCE -- Government -- National.; POLITICAL SCIENCE -- Reference.; Zionism; History; Sources